Deconstructing Duality: A Semiotic Analysis of Denotative and Connotative Meanings in Common English Proverbs - Juni Sari Sianturi; Bernieke Anggita Ristia Damanik (Young Journal of Social Sciences and Humanities, 2025)
This study aims to analyze the denotative and connotative meanings embedded in common English proverbs through a semiotic perspective. Utilizing a descriptive qualitative approach with a library research design, the data were collected from various credible sources, including scholarly journals, proverb dictionaries, and relevant reference books. The analysis is grounded in Roland Barthes’ two-tiered model of signification, which differentiates between denotation (literal meaning) and connotation (implied or symbolic meaning). The findings demonstrate that English proverbs are not merely linguistic expressions, but also cultural artifacts that convey deeply rooted moral, social, and philosophical values. Through semiotic analysis, these layered meanings can be uncovered, revealing how proverbs function as representations of collective cultural consciousness. This research thus affirms that proverbs serve as both communicative tools and vessels of cultural identity.